The Effect of Body Mass Index on Reaction Time and Response Time of the Active and Inactive Elderly - Abdalrahman Khezry; Elahe Arab Ameri; Rasoul Hammayattalab (University of Tehran, 2014)
Aging is a crucial period in human life and it is a social necessity to pay attention to the issues and needs of this stage of life. The aim of the current study was to study the effect of Body Mass Index (BMI) on reaction time and response time of the active and inactive elderly. The research method was causal-comparative and its statistical population consisted of the elderly from Mahabad city and 60 subjects were voluntarily selected and assigned to two active and inactive groups. After determining the levels of BMI, subjects of each group were divided into three levels of low, medium and high BMI and their reaction time and response time were measured. The results of t test showed that the reaction time (P=0.000) and response time (P=0.000) of the active group were significantly shorter than the inactive group. On the other hand, the results of one-way ANOVA test (to compare the reaction time between active (P=0.623) and inactive (P=0.115) elderly at different levels of BMI) showed no significant difference. For the response time, the results of one-way ANOVA showed no significant difference among active elderly (P=0.576), but there was a statistically significant difference among the inactive elderly (P=0.000). Tukey post hoc test showed that in the inactive group, those subjects with low BMI had significantly shorter response time than the subjects with medium (P=0.001) and high (P=0.000) levels of BMI. The difference between the subjects with medium and high BMI levels (P=0.669) was not significant. The results of this study showed that those individuals with low level of BMI had shorter response time than those with higher level of BMI. Overall, BMI is an effective factor for theelderly's response time and the elderly should desirably maintain their BMI by sufficient physical activity.